Repeated Nipple Fluid Aspiration: Compliance and Feasibility Results from a Prospective Multicenter Study - de Groot, J. S.; Moelans, C. B.; Elias, S. G.; Hennink, A.; Verolme, B.; Suijkerbuijk, K. P. M.; Jager, A.; Seynaeve, C.; Bos, P.; Witkamp, A. J.; Ausems, M. G. E. M.; van Diest, P. J.; et al. (PLOS ONE, 2015)
Background Despite intensive surveillance, a high rate of interval malignancies is still seen in women at increased breast cancer risk. Therefore, novel screening modalities aiming at early detection remain needed. The intraductal approach offers the possibility to directly sample fluid containing cells, DNA and proteins from the mammary ductal system where, in the majority of cases, breast cancer originates. Fluid from the breast can non-invasively be obtained by oxytocin-assisted vacuum aspiration, called nipple fluid aspiration (NFA). The goal of this feasibility study was to evaluate the potential of repeated NFA, which is a critical and essential step to evaluate its possible value as a breast cancer screening method. Methods In this multicenter, prospective study, we annually collected nipple fluid for up to 5 consecutive years from women at increased breast cancer risk, and performed a questionnaire-based survey regarding discomfort of the aspiration. Endpoints of the current interim analyses were the feasibility and results of 994 NFA procedures in 451 women with total follow-up of 560 person years of observation. Results In this large group of women at increased risk of breast cancer, repetitive NFA appeared to be feasible and safe. In 66.4% of aspirated breasts, nipple fluid was successfully obtained. Independent predictive factors for successful NFA were premenopausal status, spontaneous nipple discharge, smaller breast size, bilateral oophorectomy and previous use of hormone replacement therapy or anti-hormonal treatment. The procedure was well tolerated with low discomfort. Drop-out rate was 20%, which was mainly due to repeated unsuccessful aspiration attempts. Only 1.6% of women prematurely declined further participation because of side effects. Conclusions Repeated NFA in women at increased breast cancer risk is feasible and safe. Therefore, NFA is a promising method to non-invasively obtain a valuable source of potential breast cancer specific biomarkers.